Antecedents and outcomes of brand management from the perspective of resource based view (RBV) theory - Albert Gisip, Imelda; Harun, Amran (MCSER Publishing, 2013)
Brand management requires greater emphasis on internal factors to increase brand performance. A model of antecedents and outcomes of brand management is developed in this study based on the Resource Based View (RBV) Theory. Top management emphasis on brand, corporate supportive resources and market orientation are identified as crucial internal factors or antecedents for success of brand management. Apart from that, the brand management measurement are expanded in this study with the introduction of three new marketing constructs namely marketing capabilities, innovation and brand orientation as new dimensions in brand management which currently comprised of management related constructs. This study also contributes in the brand management of small and medium enterprise (SMEs) literature as previous studies mainly focused on the brand management for multinational companies or large organizations. One important issue of SMEs is the “internal” brand management which is currently under-researched even though it is critical in brand building and management. Therefore, this research aims to highlight the antecedents and outcomes of brand management in Malaysians’ SMEs based on RBV theory. A comprehensive literature review was done and a conceptual model is proposed in this literature review.